Design and fabrication of a preamplifier to be used with a MWPC at the ILSF. (19th April 2017) - Gol, M. Ghahremani; Ashrafi, S.; Rahighi, J.; Menk, R.H.
Abstract: The Iranian Light Source Facility (ILSF) is a new 3 GeV third generation synchrotron radiation facility in Middle East, which at the time being is in its design stage. For day one operation of the ILSF a custom made two-dimensional multiwire position sensitive detector with delay line readout will be used in small/wide angle scattering and diffraction experiments with synchrotron radiation. For many years such X-ray detectors have played an important role in these synchrotron radiation experiments and owing to their robustness they are still in use in many places. Paired with state of the art read-out electronics they are serious low cost competitors to other solutions based on solid-state hybrid pixel detectors. To achieve minimum dead time and high global count rates these detectors will require preamplifiers with certain characteristics, which involve low noise, good signal/noise ratio (better than 20 dB), high gain, short rise time (lower than 10 ns) and pulse duration shorter than 120 ns. In this paper, we present the design and first results of the evaluation of a voltage preamplifier developed at ILSF within a collaboration agreement between ILSF, Iran and the Italian Synchrotron Radiation Facility (Elettra), Italy. The application of this preamplifier in an in-house multiwire detector is discussed and results are presented.